?PREPARATION AND EVALUATION OF ALKYD RESIN FROM CASTOR OIL ? Short Communication (Biological Sciences - PJSIR, 2000)
Alkyd resin is known for its good drying performancesand good resistance to weathering and has almost replaceddrying oils as binders for gloss finishes, varnishes, woodprimers, enamels and lacquers.